Atenção nutricional na atenção primária à saúde em dois municípios da região metropolitana da Baixada Santista - Sato, Yukari [UNIFESP] (2020)
Background: Primary Health Care (PHC) is the gateway to the Health Care Network and aims to meet most health needs. Nutritional Care (NC) in PHC involves actions of food and nutrition in the promotion, protection and prevention, treatment and recovery of health. This comprehensive, intersectoral and continuous care must be provided for individuals, families and communities, according to the specificities of each group and the vulnerabilities of the different courses of life, such as in the maternal and child phase. Objective: To characterize and comparatively analyze the organization of NC to prenatal, puerperium and breastfeeding, in Primary Health Care, in two municipalities of Baixada Santista, São Paulo, Brazil. Methods: A cross-sectional, quantitative study was carried out. NC was investigated in all of the Family Health Units (FHUs) and mixed Basic Care Units (BCUs) in: Cubatão (n = 17) and Guarujá (n = 14). For this purpose, seven domains of the Instrumento de Avaliação da Organização da Atenção Nutricional (IAAN) in PHC were used, validated in its content. A descriptive analysis of the variables was performed and, in the inferential analysis, the Mann-Whitney and Pearson's Chi-square tests were used. Results: In the comparison between the municipalities, Guarujá scored better scores in all indicators. Statistically significant differences were found in NC for the following variables: Support for Nutritional Care actions: Infrastructure and Permanent Education; Food and Nutritional Surveillance; Nutritional Care for Prenatal Care and Nutritional Care for Puerperium and Breastfeeding. Conclusion: The actions of NC to the maternal and child group were more frequent in the city of Guarujá, with a higher number of nutritionists, greater workload, incorporated in NASF-AB and with more participation in A&N actions. The insertion of these professionals, however, is still incipient before the demand, in both municipalities. More investments in skilled labor, infrastructure and matrix support are needed.